Application of an ecosystem function framework to perceptions of community woodlands - Agbenyega, Olivia; Burgess, Paul J.; Cook, Matthew; Morris, Joe (Elsevier Science B.V., Amsterdam., 2009)
Owners, local residents, government, and conservation organisations can express divergent preferences in the development and management of local woodlands. The perceptions of these four groups were examined, in the context of three community woodlands in Eastern England, using an ecosystem function framework. In a pilot study, residents were able to allocate a relative importance to woodland ecosystem services which were then related to “regulation”, “habitat”, and “production” or “information” functions. However residents also placed importance on negative services or “dis-services” associated with the woodland ecosystem. Therefore a fifth category of “dis-services” was included in the main survey which included 84 local residents, three woodland owners, three government institutions, and six representatives from conservation groups. Each of the four groups placed greatest importance on services associated with habitat (16–39% of the total importance) and information (30–50%) functions suggesting, in this example, mutual interest in the use of woodlands as a habitat or recreational resource. By contrast a potential area of difference was the particularly high importance placed by one owner on dis-services such as fly tipping. In addition the woodland owners placed higher importance (10–20%), than local residents and conservation groups (7–9%), on the productive services of the wood. This suggests a need for communication when production-related operations affect recreation. The ecosystem function framework appears to be a useful approach for highlighting potential tensions and areas of mutual interest in the manage
Keywords: Ecosystem; Functions; Goods; Service; Community; Woodlands; Stakeholder; Recreation; Owner